The double-edged helix : social implications of genetics in a diverse society - Alper, Joseph S., 1946- (Johns Hopkins University Press, 2002)
Explores the impact of recent genetic discoveries on both different population segments and society as a whole. The authors address the medical and ethical implications of the new technologies, outlining positive and negative effects of genetic research on minorities, individuals with disabilities, and those of diverse sexual orientations. Presenting a wide array of perspectives, this book emphasizes the need to ensure that research into genetics does not result in discrimination against people on the basis of their DNA.